Abnormalities of Serum Fatty Acids in Children With Henoch-Schönlein Purpura by GC-MS Analysis - Min Wen; Min Wen; Shipin Feng; Xiqiang Dang; Xiqiang Dang; Xuewei Ding; Xuewei Ding; Zhiquan Xu; Xiaoyan Huang; Qiuyu Lin; Wei Xiang; Xiaoyan Li; et al. (Frontiers Media S.A., 2021)
Purpose: The objectives of this work were to test the levels of serum medium- and long- chain fatty acids (MLCFAs) in children and to discover their possible relationship with Henoch-Schönlein Purpura (HSP), also known as Immunoglobulin A vasculitis.Methods: A total of 57 children with HSP (HSP group) and 28 healthy children (CON group) were recruited for this study. Serum specimens were collected to detect the compositions and contents of MLCFAs by gas chromatography with mass spectrometry (GC-MS) analysis.Results: The contents of all detected 37 MLCFAs in the HSP group were higher than the healthy group. Thirty-one species of MLCFAs were discovered to have a significant difference (p < 0.05) in two groups. Comparing to healthy controls, there were 31, 31, 18 fatty acids showed a statistical difference in the untreated group, regular treated group, and withdrawal group of HSP, respectively. The trend of fatty acids in the three HSP groups was similar to the healthy controls, as well as the untreated group and regular treated group changed more obviously than the withdrawal group. Almitate (C16:0) and 18 carbon atoms (C18) of fatty acids were abundant in all three HSP groups, divided according to the treatment of glucocorticoid. Some fatty acids were found having considerable differences (p < 0.05) in three groups. Monounsaturated fatty acids (MUFAs), including elaidate (C18:1T), cis-11,14,17-eicosatrienoic acid ester (C20:1), and cis-15-tetracosenoate (C24:1), were distinctly higher in HSP children with renal damage.Conclusion: Our study revealed that the abnormalities in MLCFA may be associated with the development of HSP. Another interesting finding was that fatty acids contents were changing during the glucocorticoid treatment. Meanwhile, long-chain MUFAs may have an impact on renal damage in HSP patients. Further studies need to be carried out in order to explore the specific mechanism of fatty acids in the course of HSP.